2020
DOI: 10.1186/s12866-020-01935-z
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and molecular detection of extended spectrum β-lactamase producing Escherichia coli isolates from raw meat in Greater Accra region, Ghana

Abstract: Background: Typically, raw meat can be contaminated with antibiotic resistant pathogens at unhygienic slaughter and sale points. Consumption of meat contaminated with antibiotic resistant E. coli is associated with grave health care consequences. The aim of this study was to determine the microbial quality of raw meat, the antimicrobial susceptibility and Extended Spectrum Beta Lactamase (ESBL) production in E. coli isolates from raw meat. Results: Total Plate Counts exceeded the acceptable limit of 5.0 log CF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 27 publications
7
24
1
Order By: Relevance
“…Dsani et al [ 111 ] investigated the spread of E. coli isolates from raw meat in Greater Accra region in Ghana, to antibiotics resistance, respectively. Usually, raw meat can be contaminated with antibiotic resistant pathogens and consumption of meat contaminated with antibiotic resistant E. coli is associated with grave health care consequences.…”
Section: Usage Of Antibiotics In Different Countries Of Eu Region mentioning
confidence: 99%
See 1 more Smart Citation
“…Dsani et al [ 111 ] investigated the spread of E. coli isolates from raw meat in Greater Accra region in Ghana, to antibiotics resistance, respectively. Usually, raw meat can be contaminated with antibiotic resistant pathogens and consumption of meat contaminated with antibiotic resistant E. coli is associated with grave health care consequences.…”
Section: Usage Of Antibiotics In Different Countries Of Eu Region mentioning
confidence: 99%
“…Multidrug resistance (MDR) was identified in 22% of the isolates. The bla TEM gene was detected in 4% of E. coli isolates [ 111 ]. Dsani et al [ 111 ] concluded that levels of microbial contamination of raw meat in their research were unacceptable and highlighted that meat handlers and consumers are at risk of foodborne infections from E. coli including ESBL producing E. coli , which is resistant to nearly all antibiotics in use.…”
Section: Usage Of Antibiotics In Different Countries Of Eu Region mentioning
confidence: 99%
“…These practices pose the risk of bacteria developing resistance to antimicrobials. Furthermore, studies have shown the presence of antimicrobial resistance E. coli in meats and meats products in Ghana [23][24][25]. Dsani et al [23] reported that E. coli isolated from meat sources were resistant to cefuroxime (17%), sulfamethoxazole-trimethoprim (21%), tetracycline (45%) and ampicillin (57%).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown the presence of antimicrobial resistance E. coli in meats and meats products in Ghana [23][24][25]. Dsani et al [23] reported that E. coli isolated from meat sources were resistant to cefuroxime (17%), sulfamethoxazole-trimethoprim (21%), tetracycline (45%) and ampicillin (57%). Eibach et al [24] found that E. coli isolates from poultry meat were resistant to ciprofloxacin (21%) and sulfamethoxazole-trimethoprim (32%), and harbored resistance genes such as Bla SHV , bla CTX-M and bla TEM .…”
Section: Introductionmentioning
confidence: 99%
“…Globally, poultry is considered as the largest sector of the food-producing industry [6]. In addition, poultry is considered to be fed the largest amount of antibiotics and to be an important producer of animal waste, thus significantly affecting the environment and contributing to the emergence of AR and MDR bacteria [7,8].…”
Section: Introductionmentioning
confidence: 99%